(untitled) (Itinera, 2023)
This paper examines the transformative potential of performativity in reimagining the concept of dwelling and of domestic spaces. Drawing from enactivist and embodied cognition perspectives, we delve into the dynamic relationship between individuals, their bodies, and the architectural environment. Emphasising the role of bodily engagement, sensorimotor experiences, and interoceptive awareness, we explore how individuals actively participate in and shape their architectural surroundings. Moving beyond individual interactions, we also highlight the social and collective dynamics influenced by the built environment, underscoring the impact of cultural conventions and societal norms. This paper investigates some contributions that advocate for a reappropriation of institutionalised domestic spaces through imaginative interventions that challenge conventional norms and envision future-oriented dwelling practices. Within the context of institutionalised domestic spaces, we investigate the role of the fantastical and the monstrous as disordered qualities that challenge traditional boundaries and offer opportunities for transformation. Through case studies, we examine projects that blur the lines between public and private realms, enabling participatory practices and urban influences to reshape functional space utilisation. In conclusion, this paper underscores the importance of a dialogue between embodied performativity and the concept of dwelling. It proposes a re-evaluation of our relationship with space that is not just functional but enactive, and it champions the transformative potential of the arts in conceiving our future homes. With a renewed focus on sustainability, participation, and the interplay between the human body and space, we can begin to imagine a future of dwelling that is as dynamic, inclusive, and vibrant as the lives we wish to live within these spaces.